Comics and the Invisible: Introduction to the Special Issue - Piraino, Francesco; Stefanelli, Matteo (Mediascapes journal, 2023)
In contemporary visual culture, comics offer a curiously contradictory experience that is both ancient and hypermodern. It is a medium that predates film and television, and belongs to the declining circuits of print publishing, yet its market has been steadily expanding for more than two decades. It is anchored in a pre-modern and even archaic communicative practice such as drawing, yet it has been the main reservoir of ideas for major motion picture hits for more than a decade. Comics are experiencing a resurgence in consumption, institutional legitimacy, and industrial success in today's media landscape. Some even refer to it as a Renaissance or a new golden age of the Ninth Art. This is evident in the press and cultural institutions. But scholars face a dilemma: how can a medium with over a century and a half of history change so profoundly as to be “reborn” and find a new, more poignant attunement to the cultural context of an era?